Circulating Levels of Interleukin-6 and Interleukin-10, But Not Tumor Necrosis Factor-Alpha, as Potential Biomarkers of Severity and Mortality for COVID-19: Systematic Review with Meta-analysis - Udomsinprasert, Wanvisa (J Clin Immunol, 2020)
PURPOSE: Cytokine storm, an uncontrolled overproduction of inflammatory cytokines contributing to an aberrant systemic inflammatory response, is a major pathological feature of acute respiratory distress syndromes being severe manifestations of COVID-19, thus highlighting its potential as a biomarker and therapeutic target for COVID-19. We aimed to determine associations of circulating levels of inflammatory cytokines with severity and mortality of COVID-19 by systematic review and meta-analysis. METHODS: A comprehensive literature search in electronic databases consisting of PubMed, Scopus, and Cochrane Library and in a hand searching of reference lists from inception to July 31, 2020, was performed using the following search terms: COVID-19, interleukin (IL)-6, IL-10, and tumor necrosis factor-alpha (TNF-α). Mean difference (MD) from individual studies was pooled using a random-effects model. Quality assessment, publication bias, meta-regression, subgroup, and sensitivity analyses were performed. RESULTS: A total of 6212 COVID-19 patients from 24 eligible studies were included. Compared with non-severe COVID-19 patients, systemic levels of IL-6 and IL-10, but not TNF-α, were significantly elevated in severe COVID-19 patients (MD = 18.63, 95% CI: 10.91, 26.35, P < 0.00001; MD = 2.61, 95% CI: 2.00, 2.32, P < 0.00001; respectively). For COVID-19 mortality, circulating levels of IL-6, IL-10, and TNF-α were found to be significantly increased in non-survivors when compared with survivors (MD = 57.82, 95% CI: 10.04, 105.59, P = 0.02; MD = 4.94, 95% CI: 3.89, 6.00, P < 0.00001; MD = 5.60, 95% CI: 4.03, 7.17, P < 0.00001; respectively). CONCLUSION: Circulating levels of IL-6 and IL-10 might have great potential as biomarkers for the disease severity and mortality in COVID-19 patients. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10875-020-00899-z.